Methanol mediated crystal transformations in a solvatochromic metal organic framework constructed from Co(II) and 4-(4-pyridyl) benzoate - Mehlana, Gift; Ramon, Gaëlle; Bourne, Susan A. (Royal Society of Chemistry, 2016)
The structural transformations of compound 1 {[Co(44pba)2]4·(DMF)3·(EtOH)0.25·(H2O)4}n [44pba = 4-(4-pyridyl) benzoate] were followed during the exchange of DMF and ethanol molecules by methanol at room temperature. The new phases obtained 2 {[Co(44pba)2]·(MeOH)2.5·(H2O)}n, 3 {[Co(44pba)2(MeOH)2]2·(MeOH)2.5·(H2O)2}n and 4 {[Co(44pba)2(MeOH)2]·(MeOH)0.5·(H2O)0.5}n were studied using differential scanning calorimetry, thermogravimetric analysis and X-ray diffraction methods. The final phase 4 reverts back to 1 upon soaking 4 in a dry DMF–ethanol mixture as evidenced by the powder diffraction data and infrared spectra.